Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1136/emermed-2013-203046
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of unsuccessful treatment in patients with severe acute asthma

Abstract: PEFR, heart rate and other serious illnesses are the best predictors of unsuccessful treatment, but models based on these variables provide modest predictive value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…One of the recent study concluded that pre-dose PEFR, can work as an alternative primary lung function endpoint for trials in adolescent and adult patients with asthma. They demonstrated a strong association between pre-dose FEV1 and pre-dose PEFR (25).…”
Section: 3 and 4)mentioning
confidence: 96%
“…One of the recent study concluded that pre-dose PEFR, can work as an alternative primary lung function endpoint for trials in adolescent and adult patients with asthma. They demonstrated a strong association between pre-dose FEV1 and pre-dose PEFR (25).…”
Section: 3 and 4)mentioning
confidence: 96%
“…β-agonists are prescribed and given to treat airflow obstruction rapidly, while in case the patients didn't respond to β-agonists or patients exhibited moderate or severe asthma exacerbations, anticholinergics/ systemic corticosteroids are given early for treatment [13]. Inhaled βagonists and inhaled corticosteroids (ICSs) are effective in treating allergic asthma, while systematic corticosteroids (SCS) are needed to treat the infected patients [30].…”
Section: Treatmentmentioning
confidence: 99%
“…So far there have been no recognized indicators to predict the treatment response and prognosis for asthma exacerbation. In 2013, a large multicenter clinical study on severe asthma exacerbation led by Goodacre et al (67) demonstrated that, PEF rate variability and heart rate at baseline and 2 hours after treatment, and comorbidity with other severe diseases, are independent predictors of treatment failure. In 2016, a study recruiting 973 asthmatic children referred to emergency departments, identified treatment failure in 17% of all cases.…”
Section: Prognosismentioning
confidence: 99%